The reality of students' use of educational technologies in practical education lessons Usage challenges, and development prospects (Journal of Hama University, 2020)
The current research aims to study the reality of students' use of educational technologies in practical education lessons, usage challenges, and development prospects. To achieve the goals of the research, the researcher used the descriptive analytical approach, by relying on the research tool, which was represented by a questionnaire distributed to the research sample, and the number (39) supervisors to know their responses towards the reality of students' use of education technologies in practical education lessons, usage challenges, and development prospects.The study found: The reality of students' use of educational technologies in practical education lessons is generally high to medium in general from the perspective of practical education supervisors. The most important challenges facing students' use of education technologies in practical education lessons, from the viewpoint of supervisors of practical education, are: the lack of cooperation of librarians and laboratory secretaries and those responsible for education technologies with students, the lack of most educational technologies in schools, the lack of knowledge of those responsible for education technologies on how to use education technologies . The most important proposals for developing students' use of educational technologies in practical education lessons, from the viewpoint of supervisors of practical education, are: the need for those in charge of educational technologies in school to collaborate with students, employ the systemic approach when using education technologies, and train those responsible for education technologies in school on how to use education technologies to support students.